Positive electrode active material, method for manufacturing the same, positive electrode sheet, secondary battery, and electric device
Patent Information
- Application Number
- CN202310436352.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-21
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-04-21
AI Technical Summary
[0002]开发高功率性能、高循环稳定性的动力型锂离子电池是当前市场的迫切需求,然而,目前对镍钴锰酸锂三元正极材料等的含镍正极活性材料的研究中,在对功率性能有效提升时,通常会导致循环性能受损
[0021]上述说明仅是本申请实施例的技术方案的概述,为了能够更清楚了解本申请的技术手段,而可依照说明书的内容予以实施,并且为了让本申请的上述和其它目的、特征和优点能够更明显易懂,以下特举本申请的具体实施方式。
Smart Images

Figure CN118811869B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and specifically relates to a positive electrode active material, a preparation method thereof, a positive electrode plate, a secondary battery, and an electrical device. Background Art
[0002] The development of power-type lithium-ion batteries with high power performance and high cycle stability is an urgent demand in the current market. However, in current researches on nickel-containing positive electrode active materials such as nickel-cobalt-manganese ternary positive electrode materials, effective improvement of power performance usually leads to impaired cycle performance. Summary of the Invention
[0003] In view of the above problems, the present application provides a positive electrode active material, a preparation method thereof, a positive electrode plate, a secondary battery, and an electrical device, which can effectively improve power performance while maintaining good cycle performance.
[0004] In a first aspect, the embodiments of the present application provide a positive electrode active material, the positive electrode active material comprising hollow secondary particles; the hollow secondary particles comprise Li a Ni x Co y Mn z A q M p O b , 0.2≤a≤1.2, 1.8≤b≤2, 0.3≤x≤0.6, 0≤y≤0.4, 0<z≤0.4, 0≤q≤0.02, 0<p≤0.02, element A includes one or more of Al, Ti, Zr, Sr, B, La and Y, and element M includes one or more of W, Mo, Nb, Y, Ta, La, Zr and Co; the atomic percentage of element M at the grain boundary is ≥ the atomic percentage of element M in the bulk phase portion of the primary particle, and the distance from the bulk phase portion to the surface of the primary particle is equal to 5% of the volume average particle diameter Dv50 of the primary particle; element A is distributed in the hollow secondary particles in a bulk doping manner.
[0005] In the technical solutions of the embodiments of the present application, the hollow structure of the hollow secondary particles is beneficial to reducing the internal resistance of the particles, shortening the lithium ion diffusion path, facilitating the acceleration of ion transport inside the particles and improving the power performance. The positive electrode active material contains a certain amount of element M. On the one hand, it is beneficial to stabilizing the crystal form structure of the primary particles, improving the bonding strength between the primary particles and reducing the cracking and breaking of the hollow secondary particles during the cycle process, so that the cycle performance can be improved; on the other hand, it is beneficial to improving the ion transmission rate at the grain boundaries, so that the power performance can be improved. Among them, the element M is more distributed at the grain boundaries of the hollow secondary particles. Compared with the case where the element M is more distributed in the bulk phase part of the primary particles, the element M mainly distributed at the grain boundaries can better cooperate with the residual alkali of the positive electrode active material, which is beneficial to strengthening the bonding strength of the element M to the grain boundaries, so that the structure of the hollow secondary particles can be further stabilized to improve the cycle performance; it is also beneficial to increasing the ion transmission rate at the grain boundaries to improve the power performance.
[0006] Optionally, when a small amount of element A is doped in the positive electrode active material, it is also beneficial to stabilizing the crystal form structure, so that the power performance and cycle performance can be improved.
[0007] In some embodiments, the residual alkali in the positive electrode active material includes Li2CO3 and LiOH; in the positive electrode active material, the content of Li2CO3 is s, the content of LiOH is t, 0.05wt%≤s≤3wt%, 0<t≤0.4wt%; optionally, at least one of the following conditions (a1) and (a2) is satisfied; (a1) 0.05wt%≤s≤0.4wt%; (a2) 0<t≤0.25wt%. In this embodiment, the positive electrode active material has a certain content of residual alkali. On the one hand, it can better cooperate with the element M mainly distributed at the grain boundaries, which is beneficial to improving the cycle performance; on the other hand, it can provide a certain number of lithium ion transmission sites, which is beneficial to improving the power performance; in another aspect, it can attract acidic substances in the electrolyte to reduce side reactions between the hollow secondary particles and the electrolyte, which is beneficial to improving the cycle performance. The positive electrode active material with a certain content of residual alkali can provide a certain number of lithium ion transmission sites, reduce side reactions between the hollow secondary particles and the electrolyte, cooperate with the element M to strengthen the bonding strength to the grain boundaries and stabilize the structure of the hollow secondary particles; at the same time, an appropriate residual alkali content can control gas production, so that the cycle performance can be further improved.
[0008] In some embodiments, 0<q≤0.005. In this embodiment, the positive electrode active material doped with an appropriate amount of element A is beneficial to stabilizing the crystal form structure, so that the power performance and cycle performance can be improved; at the same time, the appropriate amount of element A further improves the gram capacity of the positive electrode active material.
[0009] In some embodiments, 0<p≤0.01. In this embodiment, doping an appropriate amount of element M in the positive electrode active material is beneficial to stabilizing the crystal structure of primary particles, increasing the bonding strength between primary particles to reduce cracking and fragmentation of hollow secondary particles during cycling, improving the ion transmission rate at grain boundaries, and favorably cooperating with residual alkali; meanwhile, the appropriate amount of element M further improves the specific capacity of the positive electrode active material.
[0010] In some embodiments, at least one of the following conditions (b1) to (b5) is satisfied; (b1) the volume average particle diameter Dv50 of the hollow secondary particles is 2 μm to 5 μm; (b2) the volume average particle diameter Dv50 of the hollow secondary particles is 2.5 μm to 3.5 μm; (b3) the wall thickness of the hollow secondary particles is 0.2 μm to 1.6 μm; (b4) the ratio of the cavity diameter of the hollow secondary particles to the volume average particle diameter Dv50 of the hollow secondary particles is k, where 0.1≤k≤0.8; (b5) the ratio of the cavity diameter of the hollow secondary particles to the volume average particle diameter Dv50 of the hollow secondary particles is k, where 0.5≤k≤0.8. In this embodiment, when the hollow secondary particles meet a specific volume average particle diameter, the hollow secondary particles have appropriate particle size and specific surface area, can maintain suitable electrochemical activity, so as to achieve good power performance; at the same time, side reactions can be effectively controlled. When the hollow secondary particles meet the specific wall thickness requirement, the hollow secondary particles have a relatively low wall thickness, which endows the hollow secondary particles with relatively low internal resistance and a shorter lithium ion diffusion path, so that lithium ions can be transported faster inside the hollow secondary particles, thereby achieving good power performance; when the ratio k of the cavity diameter of the hollow secondary particles to the volume average particle diameter meets a specific range, the hollow secondary particles have an appropriate relative wall thickness, which can reduce the internal stress of the material, and is beneficial to maintaining the structural stability and power performance of the material; at the same time, good power performance can be maintained.
[0011] In some embodiments, the positive electrode active material further comprises a coating layer, which is distributed on at least part of the surface of the hollow secondary particles; the coating layer comprises element Al and / or element B. In this embodiment, the coating layer can reduce the contact area between the hollow secondary particles and the electrolyte, and reduce side reactions between the hollow secondary particles and the electrolyte, thereby contributing to the improvement of cycling performance.
[0012] In some embodiments, in the positive electrode active material, the total content of Al and / or B elements in the coating layer accounts for a mass ratio of b to the positive electrode active material, satisfying at least one of the following conditions (c1) and (c2): (c1) 0 < b ≤ 5 wt%; (c2) 0.1 wt% ≤ b ≤ 2 wt%. In this embodiment, the specified elements in the coating layer satisfy an appropriate mass ratio in the positive electrode active material, which can effectively reduce the side reactions between the hollow secondary particles and the electrolyte while maintaining the specific capacity of the positive electrode active material.
[0013] In some embodiments, the coating layer satisfies at least one of the following conditions (d1) and (d2): (d1) the mass ratio of Al to B is 1 to 5; (d2) the mass ratio of Al to B is 2 to 2.5. In this embodiment, the coating layer simultaneously includes Al and B. The Al-containing compound can better reduce side reactions, and the B-containing compound can better enhance the conductivity of the material. The appropriate mass ratio of Al and B effectively improves cycle performance and also helps to improve power performance.
[0014] In some embodiments, the true density of the positive electrode active material is ≥4.6 g / cm³. 3 In this embodiment, the true density of the positive electrode active material is higher than a specific standard, resulting in a higher energy density for the positive electrode active material.
[0015] Secondly, embodiments of this application provide a positive electrode sheet, including the positive electrode sheet of the above embodiments.
[0016] Thirdly, embodiments of this application provide a secondary battery, including the positive electrode sheet of the above embodiments.
[0017] Fourthly, embodiments of this application provide an electrical device including the secondary battery described in the above embodiments.
[0018] Fifthly, this application provides a method for preparing a positive electrode active material as described in the above embodiments, comprising: heating a solution containing a transition metal salt to form a carbonate core; performing a precipitation reaction on the surface of the carbonate core to obtain a precursor whose core includes carbonate and whose shell includes hydroxide; mixing the precursor, lithium salt, material containing element A, and raw material containing element M, and sintering to obtain hollow secondary particles.
[0019] In some embodiments, at least one of the following conditions (e1) to (e3) is met: (e1) the pH value of the solution containing the transition metal salt is 10.5 to 12; (e2) the heating time of the solution containing the transition metal salt is 14 h to 25 h; (e3) the precipitation reaction time is 20 h to 28 h; and (e4) the molar ratio of the precursor to the lithium salt is 1:(1 to 1.2). In this embodiment, when at least one of the pH value of the solution containing the transition metal salt, the heating time of the solution containing the transition metal salt, and the precipitation reaction time meets specific requirements, it is beneficial to form a positive electrode active material in which the ratio k of the cavity diameter to the volume average particle size of the hollow secondary particles meets a suitable range; a suitable mass ratio of the precursor to the lithium salt is beneficial to controlling the residual alkali content in the positive electrode active material.
[0020] In some embodiments, the preparation method of the positive electrode active material further includes: mixing hollow secondary particles with raw materials for the coating layer, and sintering to obtain a positive electrode active material in which at least a portion of the surface of the hollow secondary particles is covered with a coating layer; the coating layer includes Al and / or B elements. In this embodiment, the coating layer is formed on at least a portion of the surface of the hollow secondary particles, which can reduce the contact area between the hollow secondary particles and the electrolyte, thereby reducing side reactions between the hollow secondary particles and the electrolyte and thus improving cycle performance.
[0021] The above description is merely an overview of the technical solutions of the embodiments of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, specific embodiments of this application are described below. Attached Figure Description
[0022] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0023] Figure 1 This application provides structural schematic diagrams of vehicles for some embodiments;
[0024] Figure 2 Exploded views of batteries provided for some embodiments of this application;
[0025] Figure 3 Exploded views of secondary batteries provided in some embodiments of this application;
[0026] Figure 4 This is a schematic diagram of the structure of the positive electrode sheet provided in some embodiments of this application;
[0027] Figure 5 A process flow diagram of the preparation method of the positive electrode active material provided in some embodiments of this application;
[0028] Figure 6 A process flow diagram of the preparation method of the positive electrode active material provided in some embodiments of this application;
[0029] Figure 7 This is a SEM image of the surface of the positive electrode active material prepared in Example 1 of this application;
[0030] Figure 8 This is a SEM image of the cross-section of the positive electrode active material prepared in Example 1 of this application;
[0031] Figure 9 This is another SEM image of the positive electrode active material prepared in Example 1 of this application;
[0032] Figure 10 for Figure 9 The energy spectrum at position 20 in the middle spectrum.
[0033] icon:
[0034] 1000 - Vehicles;
[0035] 100 - Battery; 200 - Controller; 300 - Motor;
[0036] 10-Box body; 11-First part; 12-Second part; 13-Accommodation space;
[0037] 20-Secondary battery; 21-Casing; 22-Electrode assembly; 23-Electrode terminals; 24-Pressure relief structure;
[0038] 211-Shell; 212-Cover;
[0039] 221-Positive electrode sheet; 2211-Positive current collector; 2212-Positive active material layer. Detailed Implementation
[0040] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0041] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.
[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.
[0043] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly indicating the number, specific order, or primary and secondary relationship of the indicated technical features.
[0044] In the description of the embodiments of this application, the technical terms "and / or", such as "feature 1 and / or feature 2", all refer to "feature 1" alone, "feature 2" alone, or "feature 1" plus "feature 2".
[0045] In the description of the embodiments of this application, unless otherwise stated, "multiple" in "one or more" means two or more.
[0046] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0047] In the embodiments of this application, the same reference numerals denote the same components, and for the sake of brevity, detailed descriptions of the same components are omitted in different embodiments. It should be understood that the height, length, width, and other dimensions of various components in the embodiments of this application shown in the accompanying drawings, as well as the overall height, length, width, and other dimensions of the integrated device, are merely illustrative and should not constitute any limitation on this application.
[0048] From a market perspective, the application of power batteries is becoming increasingly widespread. Power batteries are not only used in energy storage systems such as hydropower, thermal power, wind power, and solar power plants, but also extensively in electric vehicles such as electric bicycles, electric motorcycles, and electric cars, as well as in military equipment and aerospace. With the continuous expansion of the application areas of power batteries, the market demand is also constantly increasing.
[0049] The secondary batteries disclosed in this application can be used, but are not limited to, in electrical devices such as vehicles, ships, or aircraft. This application provides an electrical device that uses a battery as a power source. This device can be, but is not limited to, mobile phones, tablets, laptops, electric toys, power tools, electric vehicles, electric cars, ships, spacecraft, etc. Electric toys can include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Spacecraft can include airplanes, rockets, space shuttles, and spacecraft, etc.
[0050] For ease of explanation, the following embodiments use a vehicle as an example of an electrical device according to an embodiment of this application.
[0051] See Figure 1 , Figure 1 This is a schematic diagram of the structure of a vehicle 1000 provided in some embodiments of this application. The vehicle 1000 can be a gasoline-powered vehicle, a natural gas-powered vehicle, or a new energy vehicle. New energy vehicles can be pure electric vehicles, hybrid electric vehicles, or range-extended electric vehicles, etc. A battery 100 is disposed inside the vehicle 1000, and the battery 100 can be located at the bottom, front, or rear of the vehicle 1000. The battery 100 can be used to power the vehicle 1000; for example, the battery 100 can serve as the operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 200 and a motor 300. The controller 200 is used to control the battery 100 to supply power to the motor 300, for example, to meet the power needs of the vehicle 1000 during startup, navigation, and driving.
[0052] In some embodiments of this application, the battery 100 can not only serve as the operating power source for the vehicle 1000, but also as the driving power source for the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.
[0053] In this application, battery 100 refers to a single physical module comprising multiple secondary batteries 20 to provide higher voltage and capacity, which may be in the form of a battery pack, battery module, etc. Battery 100 may include a housing 10 for encapsulating the multiple secondary batteries 20, the housing 10 preventing liquids or other foreign objects from affecting the charging or discharging of the secondary batteries 20.
[0054] See Figure 2 , Figure 2This is an exploded view of a battery 100 provided in some embodiments of this application. The battery 100 includes a housing 10 and a plurality of secondary batteries 20, which are housed within the housing 10. The housing 10 is used to house the secondary batteries 20 and can have various structures. In some embodiments, the housing 10 may include a first portion 11 and a second portion 12, which overlap each other, defining a receiving space 13 for accommodating the secondary batteries 20. The second portion 12 may be a hollow structure with one open end, and the first portion 11 may be a plate-like structure, overlapping the open side of the second portion 12 to form a housing 10 with the receiving space 13; alternatively, the first portion 11 and the second portion 12 may both be hollow structures with one open side, overlapping the open side of the second portion 12 to form a housing 10 with the receiving space 13. Of course, the first portion 11 and the second portion 12 can have various shapes, such as cylinders, cuboids, etc.
[0055] In battery 100, multiple secondary batteries 20 can be connected in series, parallel, or in a mixed configuration. A mixed configuration means that some of the secondary batteries 20 are connected in series while others are connected in parallel. Multiple secondary batteries 20 can be directly connected in series, parallel, or in a mixed configuration, and then the entire assembly of the multiple secondary batteries 20 is housed within the housing 10. Alternatively, multiple secondary batteries 20 can first be connected in series, parallel, or in a mixed configuration to form modules, and then these modules can be connected in series, parallel, or in a mixed configuration to form a whole, which is then housed within the housing 10. Battery 100 may also include other structures; for example, multiple secondary batteries 20 can be electrically connected through a busbar component to achieve parallel, series, or mixed configurations of the multiple secondary batteries 20.
[0056] The secondary battery 20 refers to the smallest unit that makes up the battery pack. It can be a lithium-sulfur battery, a sodium-ion battery, or a magnesium-ion battery, but is not limited to these.
[0057] See Figure 3 The secondary battery 20 may include a housing 21, an electrode assembly 22, and an electrolyte, with the electrode assembly 22 and the electrolyte both housed within the housing 21.
[0058] The outer casing 21 may include a housing 211 and a cover 212. The housing 211 is an assembly that fits with the cover 212 to form an internal sealed space for the secondary battery 20, wherein the formed sealed space can accommodate the electrode assembly 22, electrolyte, and other components. The cover 212 is a component that closes onto the opening of the housing 211 to isolate the internal environment of the secondary battery 20 from the external environment. The shape of the cover 212 may be adapted to the shape of the housing 211 to fit the housing 211, and the cover 212 may also be provided with functional components such as electrode terminals 23 and pressure relief structures 24. A sealing ring may be provided between the opening of the housing 211 and the cover 212 to achieve a seal between the housing 211 and the cover 212.
[0059] The housing 211 and cover 212 can be of various shapes and sizes, such as cuboids, cylinders, and hexagonal prisms. Specifically, the shapes of the housing 211 and cover 212 can be determined according to the specific shape and size of the electrode assembly 22. The materials of the housing 211 and cover 212 can be various, such as, but not limited to, metals like copper, iron, aluminum, stainless steel, and aluminum alloys. The materials of the sealing ring can be various, such as, but not limited to, materials resistant to electrolyte corrosion, high toughness, and fatigue resistance, such as PP (polypropylene), PC (polycarbonate), and PET (polyethylene terephthalate). A plating layer can be formed on the outer surface of the housing 211, and the plating layer material can be various, such as, but not limited to, corrosion-resistant materials like Ni and Cr.
[0060] The secondary battery 20 can also be in a pouch form, such as a bag-style pouch. The pouch material can be plastic, and examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0061] The electrode assembly 22 may consist of a positive electrode 221, a negative electrode, and a separator. The secondary battery 20 mainly relies on the movement of metal ions between the positive and negative electrode 221 to operate. During charging and discharging, active ions repeatedly insert and extract between the positive and negative electrode 221; the separator is disposed between the positive and negative electrode 221, mainly to prevent short circuits between the positive and negative electrodes, while allowing ions to pass through. The electrode assembly 22 may be a wound structure or a stacked structure, and the embodiments of this application are not limited to this.
[0062] See Figure 4The positive electrode 221 includes a positive current collector 2211 and a positive active material layer 2212 disposed on the surface of the positive current collector 2211. The positive current collector 2211 has two surfaces opposite each other in its own thickness direction, and the positive active material layer 2212 is disposed on either or both of the two opposite surfaces of the positive current collector 2211. The positive current collector 2211 can be a metal foil or a composite current collector. The material of the positive current collector 2211 in the form of a metal foil can be aluminum. The composite current collector can include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector can be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.). The positive electrode active material in the positive electrode active material layer 2212 may include the positive electrode active material provided in the embodiments of this application, and may also include positive electrode active material materials such as lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, and lithium sulfur. In some embodiments, the positive electrode active material layer 2212 may optionally include a binder. As an example, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin. In some embodiments, the positive electrode active material layer 2212 may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0063] The negative electrode sheet includes a negative current collector and a negative active material layer disposed on the surface of the negative current collector. The negative current collector has two surfaces opposite each other in its own thickness direction, and the negative active material layer is disposed on either or both of the two opposite surfaces of the negative current collector. The negative current collector can be a metal foil or a composite current collector. The material of the negative current collector in the form of a metal foil can be copper. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.). The negative active material in the negative active material layer can be a negative active material such as carbon or silicon. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. Silicon-based materials may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials may also be used. These negative electrode active materials may be used alone or in combination of two or more. In some embodiments, the negative electrode active material layer may also optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS). In some embodiments, the negative electrode active material layer may also optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the negative electrode active material layer may also optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0064] This application does not impose any particular restrictions on the type of separator membrane; any known porous separator membrane with good chemical and mechanical stability can be selected.
[0065] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0066] The electrolyte acts as a conductor of ions between the positive electrode 221 and the negative electrode. In some embodiments, the electrolyte includes an electrolyte salt and a solvent, and there are no specific limitations on the types of electrolyte salt and solvent, which can be selected according to requirements.
[0067] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0068] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0069] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain performance of the secondary battery 20, such as additives that improve the overcharge performance of the secondary battery 20, additives that improve the high-temperature or low-temperature performance of the secondary battery 20, etc.
[0070] With the continued strong performance of the new energy vehicle market, the demand for power batteries is growing daily, making the development of high-power lithium-ion batteries with high cycle stability an urgent market need. Among them, nickel-containing cathode active materials, such as lithium nickel cobalt manganese oxide ternary cathode materials, have attracted much attention due to their advantages such as large specific capacity, high energy density, and high output power.
[0071] To improve the power performance and cycle stability of nickel-containing cathode active materials such as lithium nickel cobalt manganese oxide ternary cathode materials, some studies have focused on: controlling particle size to enhance electrochemical reactivity, doping to stabilize crystal structure, coating to suppress side reactions, and constructing porous or hollow polycrystalline particles to improve ion transport rates. However, increased reactivity can lead to more severe side reactions, and the suppression effect of coating layers alone on side reactions is very limited. Polycrystalline particles with porous or hollow structures are prone to cracking and breakage during repeated high-voltage charge-discharge cycles. Meanwhile, improving the ion transport rate at the grain boundaries of polycrystalline particles remains a significant challenge. In other words, some approaches fail to effectively improve power performance and cycle performance; while in other approaches, while effectively improving power performance, it often results in compromised cycle performance.
[0072] Based on this, the embodiments of the present application propose a positive electrode active material, which includes hollow secondary particles, with a certain amount of specific element M mainly distributed at the grain boundaries of the hollow secondary particles. Optionally, a small amount of specific element A is doped, and optionally, a certain content of residual alkali in the positive electrode active material is regulated. The hollow structure of the hollow secondary particles is beneficial to reducing the internal resistance of the particles, shortening the diffusion path of lithium ions, accelerating the transmission of ions inside the particles, and thus improving the power performance. On the basis of the hollow structure, the element M or the M-containing compound is beneficial to improving the bonding strength between primary particles, so as to reduce the cracking and breaking of the hollow secondary particles during the cycle process; a certain amount of residual alkali can also cooperate with the element M or the M-containing compound, which is beneficial to strengthening the bonding strength of the element M or the M-containing compound to the grain boundaries, thereby effectively improving the cycle performance. In addition, the element A is also beneficial to stabilizing the crystal structure and improving the cycle performance; the element M or the M-containing compound also has the functions of stabilizing the crystal structure of the primary particles and improving the ion transmission rate at the grain boundaries, which is beneficial to improving the power performance and cycle performance; a certain amount of residual alkali can provide certain lithium ion transmission sites, can attract acidic substances in the electrolyte to reduce side reactions between the hollow secondary particles and the electrolyte, and is beneficial to improving the power performance and cycle performance.
[0073] The positive electrode active material proposed by the embodiments of the present application and the preparation method thereof will be described in detail below.
[0074] In a first aspect, the embodiments of the present application provide a positive electrode active material, the positive electrode active material includes hollow secondary particles; the hollow secondary particles include Li a Ni x Co y Mn z A q M p O b , 0.2≤a≤1.2, 1.8≤b≤2, 0.3≤x≤0.6, 0≤y≤0.4, 0<z≤0.4, 0≤q≤0.02, 0<p≤0.02, the element A includes one or more of Al, Ti, Zr, Sr, B, La and Y, and the element M includes one or more of W, Mo, Nb, Y, Ta, La, Zr and Co; the atomic percentage of the element M at the grain boundary is ≥ the atomic percentage of the element M in the bulk phase part of the primary particle, and the distance from the bulk phase part to the surface of the primary particle is equal to 5% of the volume average particle diameter Dv50 of the primary particle; the element A is distributed in the hollow secondary particles in a bulk phase doping manner.
[0075] The hollow secondary particle refers to an agglomerated secondary particle with a cavity inside, and the secondary particle is formed by aggregation of primary particles; the primary particle refers to a non-agglomerated particle, that is, a single fine crystal grain. The hollow secondary particle is a particle with a cavity inside formed by agglomeration of single fine crystal grains.
[0076] In the embodiments of this application, the hollow secondary particles include Li a Ni x Co y Mn z A q M p O b The component testing method for molecular formulas can refer to conventional methods. For example, ICP emission spectroscopy can be used for testing.
[0077] It should be noted that the ratio of each element in the positive electrode active material in this application refers to the ratio of each element in the positive electrode active material before it is formed into a positive electrode sheet 221 and assembled into a secondary battery 20. Those skilled in the art will understand that some elements will be consumed in the positive electrode sheet 221, the secondary battery 20, and the electrical equipment due to the formation and cycling processes. Therefore, even if the ratio of the corresponding elements in the positive electrode active material is not found to be within the above range, it should still fall within the scope of this application.
[0078] It should be noted that in the positive electrode 221, the secondary battery 20, and the electrical equipment, lithium ions are consumed during formation and cycling processes, resulting in a lithium content (a) in the measured positive electrode active material being less than 1. Conversely, if lithium is replenished to both the positive and negative electrode 221, after formation and cycling processes, the lithium content (a) in the measured positive electrode active material may be greater than 1.
[0079] In the embodiments of this application, the molar coefficient α of the Li (lithium) element takes the value of any one of 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.95, 1, 1.05, 1.1, 1.15 and 1.2 or a range between any two.
[0080] It should be noted that in the positive electrode 221, secondary battery 20, and electrical equipment, due to the cycling process, oxygen elements in the positive electrode active material are lost, which may result in the measured oxygen content b in the positive electrode active material being less than 2.
[0081] In the embodiments of this application, the molar coefficient b of the O (oxygen) element is, for example, but not limited to, any one of 1.8, 1.85, 1.9, 1.95 and 2, or a range between any two.
[0082] The molar coefficient x of Ni can take values such as, but not limited to, any one of 0.3, 0.35, 0.4, 0.45, 0.5, 0.55 and 0.6 or any range between two of them.
[0083] The molar coefficient y of Co (cobalt) can be 0, which means that the molecular formula of the hollow secondary particles may not contain Co. The value of this coefficient y is, for example, but not limited to, any one of 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35 and 0.4 or any range between two of them.
[0084] The molar coefficient z of Mn (manganese) can take, for example, but not limited to, any one of the following points or any range between two: 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35 and 0.4.
[0085] Element A refers to a specified class of elements, such as those bulk-doped into primary particles. The molar coefficient q of element A can be 0, meaning that the molecular formula of the hollow secondary particles may not contain element A. The value of this coefficient q is, for example, but not limited to, any one of 0, 0.005, 0.01, 0.015, and 0.02, or a range between any two.
[0086] Element M refers to another class of specified elements that are mainly distributed at the grain boundaries of hollow secondary particles; the molar coefficient p of element M can take, for example, but is not limited to, any one of 0.005, 0.01, 0.015 and 0.02 or any range between two of them.
[0087] The distribution of element A in the hollow secondary particles as a bulk dopant means that the content of element A is similar throughout the hollow secondary particles, and it is distributed in a relatively uniform manner throughout the hollow secondary particles.
[0088] The atomic percentage of element M at the grain boundary is greater than or equal to the atomic percentage of element M in the bulk phase of the primary grain. In other words, element M is more distributed at the grain boundary of the hollow secondary grain.
[0089] The method for testing the atomic percentage of element M at different positions can refer to conventional methods. For example, an SEM image of the cross-section of the positive electrode active material can be obtained, and the atomic percentage of element M at different positions can be obtained by analyzing the spectrum.
[0090] The volume average particle size Dv50 refers to the particle size corresponding to 50% of the volume distribution. It can be determined using conventional methods. As an example, referring to GB / T 19077-2016 / ISO 13320:2009 Particle size distribution laser diffraction method, the measurement is performed using a Malvern 3000 instrument.
[0091] The distance from the bulk phase to the surface of the primary particle is equal to 5% of the volume average particle size Dv50 of the primary particle. In other words, the diameter of the bulk phase is 90% of the volume average particle size Dv50 of the primary particle.
[0092] In some embodiments of this application, the grain boundaries of the positive electrode active material include: grain boundaries located outside the hollow secondary particles, grain boundaries located inside the hollow secondary particles and at the junction with the hollow cavity, and grain boundaries located inside the hollow secondary particles that are in contact with each other.
[0093] It should be noted that, in some embodiments of this application, element M may be, for example, an oxide MO. n1 Or lithium metal oxide Li n2 MO n3 The form (n1, n2 and n3 are all greater than 0) exists. Therefore, when confirming the molecular formula of hollow secondary particles by ICP emission spectroscopy, the detection results show that x+y+z+q<1 and x+y+z+q+p>1.
[0094] In the technical solution of this application embodiment, the hollow structure of the hollow secondary particles is beneficial to reducing the internal resistance of the particles, shortening the lithium ion diffusion path, and accelerating the transport of ions inside the particles, thereby improving power performance.
[0095] The positive electrode active material contains a certain amount of element M. While maintaining a high discharge capacity, it helps stabilize the crystal structure of the primary particles and improves the bonding strength between the primary particles, thereby reducing the cracking and breakage of the hollow secondary particles during cycling and thus improving cycle performance. On the other hand, it helps improve the ion transport rate at the grain boundaries, thereby improving power performance.
[0096] Among them, element M is more distributed at the grain boundaries of hollow secondary particles, compared to element M which is more distributed in the bulk phase of primary particles. Element M, which is mainly distributed at the grain boundaries, can better cooperate with the residual alkali of the positive electrode active material, which is conducive to strengthening the adhesion strength of element M to the grain boundaries, thereby further stabilizing the structure of hollow secondary particles and improving cycle performance; it is also conducive to improving the ion transport rate at the grain boundaries and thus improving power performance.
[0097] Optionally, doping the positive electrode active material with a small amount of element A can also help stabilize the crystal structure, thereby improving power performance and cycle performance.
[0098] In some embodiments, the residual alkali in the positive electrode active material includes Li2CO3 and LiOH; in the positive electrode active material, the content of Li2CO3 is s, and the content of LiOH is t, where 0.05wt%≤s≤3wt%, 0<t≤0.4wt%. Optionally, at least one of the following conditions (a1) and (a2) is satisfied; (a1) 0.05wt%≤s≤0.4wt%; (a2) 0<t≤0.25wt%.
[0099] In some embodiments of the present application, the residual alkali is mainly distributed at the grain boundaries of the hollow secondary particles, and the content of the residual alkali in the positive electrode active material can be detected by referring to a conventional method. As an example, it can be measured using the general method for determining acidity and alkalinity of chemical reagents (GB / T 9724-2007). The content s of Li2CO3 in the positive electrode active material is, for example but not limited to, any one point value selected from 0.05wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, and 4wt%, or a range value between any two thereof.
[0100] The content t of LiOH in the positive electrode active material is, for example but not limited to, any one point value selected from 0.05wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt% and 0.4wt%, or a range value between any two thereof.
[0101] Regarding condition (a1), optionally, 0.1wt%≤s≤0.4wt%.
[0102] Regarding condition (a2), optionally, 0.05wt%<t≤0.25wt%.
[0103] In this embodiment, the positive electrode active material has a certain content of residual alkali. On the one hand, it can better cooperate with the element M mainly distributed at the grain boundaries, which is beneficial to improving the cycle performance; on the other hand, it can provide a certain number of lithium ion transmission sites, which is beneficial to improving the power performance; in another aspect, it can attract acidic substances in the electrolyte to reduce side reactions between the hollow secondary particles and the electrolyte, which is beneficial to improving the cycle performance. The positive electrode active material with a certain content of residual alkali can provide a certain number of lithium ion transmission sites, reduce side reactions between the hollow secondary particles and the electrolyte, cooperate with the element M to strengthen the bonding strength of grain boundaries and stabilize the structure of the hollow secondary particles; at the same time, an appropriate residual alkali content can control gas generation, thereby further improving the cycle performance.
[0104] In some embodiments, 0 <q≤0.005。
[0105] As an example, the value of q can be, for example, but not limited to, any point value of 0.001, 0.002, 0.003, 0.004, and 0.005, or a range of values between any two.
[0106] In this embodiment, doping the positive electrode active material with an appropriate amount of element A is beneficial to stabilizing the crystal structure, thereby improving power performance and cycle performance; at the same time, an appropriate amount of element A further improves the specific capacity of the positive electrode active material.
[0107] In some embodiments, 0 <p≤0.01。
[0108] As an example, the value of p can be, for example, but not limited to, any one of the point values of 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009 and 0.01, or a range of any two.
[0109] In this embodiment, doping the positive electrode active material with an appropriate amount of element M is beneficial to stabilizing the crystal structure of the primary particles, improving the bonding strength between the primary particles and reducing the cracking and breakage of the hollow secondary particles during cycling, improving the ion transport rate at the grain boundaries, and better cooperating with residual alkali; at the same time, an appropriate amount of element M further improves the specific capacity of the positive electrode active material.
[0110] In some embodiments, element M is added and distributed primarily in the form of compounds containing element M, and in the positive electrode active material, the content of compounds containing element M is ≤2wt% (0 < 0 < 2wt%).
[0111] Compounds containing element M include, for example, MO. n1 and Li n2 MO n3 One or more of (n1, n2 and n3 are all greater than 0).
[0112] As an example, the content of the compound containing element M in the positive electrode active material is, for example, but not limited to, any one of 0.5 wt%, 1 wt%, 1.5 wt%, and 2 wt%, or a range between any two.
[0113] In some embodiments, at least one of the following conditions (b1) to (b5) is satisfied: (b1) the volume average particle size Dv50 of the hollow secondary particles is 2 μm to 5 μm; (b2) the volume average particle size Dv50 of the hollow secondary particles is 2.5 μm to 3.5 μm; (b3) the wall thickness of the hollow secondary particles is 0.2 μm to 1.6 μm; (b4) the ratio of the cavity diameter of the hollow secondary particles to the volume average particle size Dv50 of the hollow secondary particles is k, 0.1 ≤ k ≤ 0.8; (b5) the ratio of the cavity diameter of the hollow secondary particles to the volume average particle size Dv50 of the hollow secondary particles is k, 0.5 ≤ k ≤ 0.8.
[0114] The volume average particle size Dv50 of the hollow secondary particles can take, for example, but not limited to, any one of 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm and 5μm, or a range between any two.
[0115] The wall thickness of hollow secondary particles refers to the wall thickness from the inner interface to the outer surface of the particle. It can be obtained by subtracting the size of the hollow cavity from the volume average particle size Dv50 and then dividing by 2. Multiple calculations can be obtained first, and then the average value can be taken. The size of the hollow cavity refers to the dimension corresponding to a straight line passing through the center of the hollow cavity and extending to both ends of the cavity.
[0116] Regarding the wall thickness of the hollow secondary particles, its value is, for example, but not limited to, any one of 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm and 1.6μm, or a range between any two.
[0117] Regarding the value of k, its value can be, for example, but not limited to, any point value or a range between any two of 0.1, 0.2, 0.3, 0.4, 0.5, 0.6 and 0.7, 0.8.
[0118] As an example, hollow secondary particles satisfy the following conditions: the volume average particle size Dv50 of the hollow secondary particles is 2.5μm to 3.5μm; the wall thickness of the hollow secondary particles is 0.2μm to 1.6μm; and the ratio of the cavity diameter of the hollow secondary particles to the volume average particle size Dv50 of the hollow secondary particles is k, where 0.5≤k≤0.8.
[0119] In this embodiment, when the hollow secondary particles meet a specific volume average particle size, they have a more suitable particle size and specific surface area, maintaining appropriate electrochemical activity, thereby achieving better power performance and improving side reaction problems. When the hollow secondary particles meet a specific wall thickness requirement, they have a lower wall thickness, resulting in lower internal resistance and a shorter lithium-ion diffusion path, allowing lithium ions to be transported more quickly within the hollow secondary particles, thus achieving better power performance. When the ratio k of the cavity diameter to the volume average particle size of the hollow secondary particles meets a specific range, the hollow secondary particles have a suitable relative wall thickness, which can reduce the internal stress of the material, helping to maintain the structural stability and power performance of the material; at the same time, it can maintain good power performance.
[0120] In some embodiments, the positive electrode active material further includes a coating layer distributed on at least a portion of the surface of the hollow secondary particles; the coating layer includes Al and / or element B.
[0121] The coating layer is distributed on at least part of the surface of the main material; that is, the coating layer can partially cover the surface of the main material or completely cover the surface of the main material.
[0122] The cladding layer may include Al (aluminum) element, or B (boron) element, or both Al and B elements.
[0123] Al is added to the coating layer, for example, in the form of Al-containing compounds such as γ-Al2O3, and the final coating layer contains Al in the form of γ-Al2O3 and / or LiAlO2; B is added to the coating layer, for example, in the form of B-containing compounds such as H3BO3, and the final coating layer contains B in the form of H3BO3 and / or Li3BO3.
[0124] In some embodiments of this application, the coating layer is a structure that coats at least part of the surface of the hollow secondary particles. It can be observed that some of the coating material is distributed in the form of small particles on the surface of the hollow secondary particles. The interface between the two can be determined by conventional methods, such as directly observing the cross-section of the material using a scanning electron microscope.
[0125] In this embodiment, the coating layer can reduce the contact area between the hollow secondary particles and the electrolyte, and can reduce the side reactions between the hollow secondary particles and the electrolyte, thereby improving the cycle performance.
[0126] In some embodiments, in the positive electrode active material, the total content of Al and / or B elements in the coating layer accounts for a mass ratio of b of the positive electrode material, satisfying at least one of the following conditions (c1) and (c2): (c1) 0 < b ≤ 5 wt%; (c2) 0.1 wt% ≤ b ≤ 2 wt%.
[0127] As an example, the total content of Al and / or B elements in the coating layer as a percentage of the mass of the cathode material, b, may be, for example, but not limited to, any one of 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, and 5wt%, or a range between any two.
[0128] In this embodiment, the specified elements in the coating layer meet the appropriate mass ratio in the positive electrode active material, which can effectively reduce the side reactions between the hollow secondary particles and the electrolyte, while maintaining the specific capacity of the positive electrode active material.
[0129] In some embodiments, at least one of the following conditions (d1) and (d2) is satisfied in the coating layer: (d1) the mass ratio of Al to B is 1 to 5; (d2) the mass ratio of Al to B is 2 to 2.5.
[0130] As an example, the quality ratio of Al to B is, for example, but not limited to, any one of the point values of 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 and 5, or any range of values between the two.
[0131] In this embodiment, the coating layer includes both Al and B. Compounds containing Al can effectively reduce side reactions, while compounds containing B can effectively enhance the conductivity of the material. The combination of Al and B in a suitable mass ratio can effectively improve cycle performance and also improve power performance.
[0132] In some embodiments, the true density of the positive electrode active material is >4.6 g / cm³. 3 .
[0133] The true density of a positive electrode active material refers to the actual mass of a unit volume of solid material in an absolutely dense state, which can be obtained by methods such as, but not limited to, impregnation and gas volume methods.
[0134] In this embodiment, the true density of the positive electrode active material is higher than a specific standard, which gives the positive electrode active material a high energy density.
[0135] Secondly, embodiments of this application provide a positive electrode 221, including the positive electrode 221 of the above embodiments.
[0136] Thirdly, embodiments of this application provide a secondary battery 20, including the positive electrode 221 of the above embodiments.
[0137] Fourthly, this application provides an electrical device including the secondary battery 20 described in the above embodiments.
[0138] Fifthly, embodiments of this application provide a method for preparing a positive electrode active material as described in the above embodiments, see [link to previous document]. Figure 5 The process includes: heating a solution containing transition metal salts to form a carbonate core; a precipitation reaction occurring on the surface of the carbonate core to obtain a precursor whose core includes carbonate and whose shell includes hydroxide; and mixing the precursor, lithium salt, material containing element A (referred to as A source), and raw material containing element M (referred to as M source) and sintering them to obtain hollow secondary particles.
[0139] In solutions containing transition metal salts, the types of transition metals can be adjusted using the chemical formula of hollow secondary particles. For example, nickel, cobalt, and manganese salts can be controlled according to a specific molar ratio of nickel, cobalt, and manganese elements; wherein the molar percentage of cobalt and manganese can be 0 independently.
[0140] In the process of heating a solution containing transition metal salts to form a carbonate core, for example, a certain concentration of carbonic acid solution is used as a first-stage precipitant and a certain concentration of ammonia water is used as a complexing agent. The mixture is heated under a protective gas condition and accompanied by stirring for a period of time to form a carbonate core with a loose structure.
[0141] During the precipitation reaction on the surface of the carbonate core, for example, sodium hydroxide solution can be used as a second-stage precipitant to continue the precipitation reaction. Then, after washing, filtering, and drying, a precursor is obtained, consisting of a loose carbonate core and a dense hydroxide shell.
[0142] It should be noted that during the mixing of the precursor, lithium salt, material containing element A, and raw material containing element M, the lithium salt includes, for example, one or more of lithium carbonate and lithium hydroxide; when the molar coefficient q of element A in the chemical formula of the hollow secondary particles is 0, the amount of material containing element A is 0; when the molar coefficient p of element M in the chemical formula of the hollow secondary particles is 0, the amount of material containing element M is 0.
[0143] In some embodiments, at least one of the following conditions (e1) to (e3) is satisfied: (e1) the pH value of the solution containing the transition metal salt is 10.5 to 12; (e2) the heating time of the solution containing the transition metal salt is 14 h to 25 h; (e3) the precipitation reaction time is 20 h to 28 h; (e4) the molar ratio of the precursor to the lithium salt is 1:(1 to 1.2).
[0144] Regarding condition (e1), the pH value of the solution containing the transition metal salt is, for example, but not limited to, any one of 10.5, 11, 11.5 and 12, or a range between any two.
[0145] Regarding condition (e2), the heating time of the solution containing the transition metal salt is, for example, but not limited to, any one of 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h and 25h, or a range between any two.
[0146] Optionally, during the heating of the solution containing the transition metal salt, the heating temperature is 30°C to 80°C, accompanied by stirring at a speed of 200 rpm to 800 rpm.
[0147] Regarding condition (e3), the time for precipitation to occur is, for example, but not limited to, any one of 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h and 28h, or a range between any two.
[0148] Optionally, during the precipitation reaction, the pH of the system is 11.2 to 12.8, the heating temperature is 30°C to 80°C, and the stirring speed is 400 rpm to 900 rpm.
[0149] Regarding condition (e4), the molar ratio of the precursor to the lithium salt is, for example, but not limited to, any one of 1:1, 1:1.05, 1:1.1, 1:1.15 and 1:1.2, or a range between any two.
[0150] Optionally, in the embodiments of this application, during the sintering process to obtain hollow secondary particles, the sintering temperature is 700℃~950℃ and the sintering time is 9h~14h.
[0151] In this embodiment, when at least one of the pH value of the solution containing the transition metal salt, the heating time of the solution containing the transition metal salt, and the precipitation reaction time meets specific requirements, it is beneficial for the positive electrode active material to form a cavity diameter to volume average particle size ratio k of hollow secondary particles that meets a suitable range; a suitable mass ratio of precursor to lithium salt is beneficial for controlling the residual alkali content in the positive electrode active material.
[0152] See Figure 6 In some embodiments, where the positive electrode active material further includes a coating layer, as an example, the preparation method of the positive electrode active material further includes: mixing hollow secondary particles with the raw materials of the coating layer, and sintering to obtain a positive electrode active material in which at least a portion of the surface of the hollow secondary particles is covered with a coating layer.
[0153] Optionally, in the embodiments of this application, during the process of sintering the positive electrode active material in which at least a portion of the surface of the hollow secondary particles is covered with a coating layer, the sintering temperature is 350℃~500℃ and the sintering time is 4h~8h.
[0154] In this embodiment, a coating layer is formed on at least a portion of the surface of the hollow secondary particles. The coating layer can reduce the contact area between the hollow secondary particles and the electrolyte, thereby reducing the side reactions between the hollow secondary particles and the electrolyte and thus improving the cycle performance.
[0155] The following specific embodiments are provided to better illustrate this application.
[0156] I. Preparation of secondary batteries
[0157] (1) Preparation of positive electrode active materials
[0158] Example 1
[0159] 1) Prepare a solution containing transition metal salts by weighing the appropriate transition metal salts according to a nickel-cobalt-manganese molar ratio of 3:3:3. The total metal concentration of the solution containing transition metal salts is 2 mol / L, and the addition rate is 12 L / h. Prepare a 1.6 mol / L sodium carbonate solution as a first-stage precipitant, adding it at a rate of 20 L / h. Simultaneously, add 25% ammonia water as a complexing agent at a rate of 2 L / h. Under a nitrogen protective atmosphere, add the three solutions to a reactor containing 95 L of deionized water at 50 °C. Control the stirring speed at 450 rpm, adjust the pH value of the reaction to stabilize at 11.5, and continuously stir the reaction for 18 h to obtain a carbonate core with a loose structure.
[0160] 2) Using 4.5 mol / L sodium hydroxide solution as a two-stage precipitant, the addition rate was controlled at 9 L / h, the reaction pH was adjusted to 11.8, and the reaction was carried out at 50℃ and nitrogen protection atmosphere with a stirring speed of 600 rpm for 26 h. After aging for 2 h, the precursor was washed, filtered and dried to obtain a precursor with a loose carbonate core and a dense hydroxide shell.
[0161] 3) Weigh the obtained precursor, lithium hydroxide (LiOH) and titanium oxide (TiO2) in a molar ratio of 1:1.15:0.001, then add 0.65 wt% of tungsten trioxide (WO3) from the precursor, mix and stir evenly, then heat to 900℃ at a heating rate of 2℃ / min under air or oxygen atmosphere, hold for 12h, and finally cool naturally to room temperature to obtain hollow secondary particles after one sintering.
[0162] 4) The hollow secondary particles obtained after one sintering, Al element (derived from γ-Al2O3) and B element (derived from H3BO3) are mixed evenly in a mass ratio of 1:0.004:0.002. The mixture is heated to 450℃ at a heating rate of 2℃ / min and held at that temperature for 6h. Finally, it is naturally cooled to room temperature to obtain a positive electrode active material with a coating layer.
[0163] Examples 2 to 5
[0164] The difference from Example 1 is that the pH value of the solution containing the transition metal salt and the heating and stirring reaction time are different in step 1), resulting in positive electrode active materials with different k values of hollow secondary particles.
[0165] Examples 6 to 8
[0166] The difference from Example 1 is that: step 1) the heating and stirring reaction time is different; step 2) the precipitation reaction time is different, resulting in positive electrode active materials with different volume average particle size Dv50 of hollow secondary particles.
[0167] Examples 9 to 11
[0168] The difference from Example 1 is that the molar ratio of nickel, cobalt and manganese added in step 1) is different, and the sintering temperature in step 3) is modified to 830℃, 850℃ and 890℃ respectively.
[0169] Example 12
[0170] The difference from Example 1 is that the heating and stirring reaction time in step 1) and the heating and stirring time in step 2) are different.
[0171] Examples 13-14
[0172] The difference from Example 1 is that the pH values of the solutions containing transition metal salts in step 1) are different, being 10.0 and 9.5 respectively.
[0173] Examples 15-16
[0174] The difference from Example 1 is that the molar ratio of the precursor to titanium oxide (TiO2) added in step 3) is different, being 1:0.02 and 1:0.01 respectively.
[0175] Examples 17-18
[0176] The difference from Example 1 is that the titanium oxide (TiO2) added in step 3) is replaced with zirconium oxide (ZrO2) and yttrium oxide (Y2O3), respectively.
[0177] Examples 19 to 21
[0178] The difference from Example 1 is that the content of the M source (WO3) added in step 3) is changed to 1.5 wt%, 1.0 wt%, and 0.1 wt%, respectively.
[0179] Examples 22 to 24
[0180] The difference from Example 1 is that the M source (WO3) added in step 3) is replaced with Nb2O5 oxide, MoO3 and ZrO2 respectively.
[0181] Example 25
[0182] The difference from Example 1 is that no material containing element A is added in step 2).
[0183] Examples 26-27
[0184] The difference from Example 1 is that the molar ratio of the precursor material added in step 3) to lithium hydroxide is 1:1.18 and 1:1.13, respectively.
[0185] Example 28
[0186] The difference from Example 1 is as follows:
[0187] The sintering temperature in step 3) is 800℃.
[0188] Example 29
[0189] The difference from Example 1 is that the sintering temperature in step 3) is 1000℃.
[0190] Example 30
[0191] The difference from Example 1 is that the molar ratio of the precursor material added in step 3) to lithium hydroxide is 1:1.
[0192] Examples 31 to 41
[0193] The difference from Example 1 is that the amount and ratio of Al (derived from γ-Al2O3) and B (derived from H3BO3) added in step 4) are different.
[0194] Comparative Example 1
[0195] The difference from Example 1 is that no material containing element M is added in step 2).
[0196] Comparative Example 2
[0197] The difference from Example 1 is that in step 1), (NH4)6W7O is simultaneously mixed into the transition metal salt at a mass ratio of 1 wt%. 24In preparation step 2), no material containing element M is added, and the sintering temperature is changed to 850℃ to avoid the segregation of element M during sintering and to ensure that element M mainly exists in the bulk phase.
[0198] The descriptions of the various embodiments and comparative examples above tend to emphasize the differences between the various embodiments and comparative examples. Their similarities or similarities can be referred to each other. For the sake of brevity, these will not be repeated here.
[0199] (2) Preparation of positive electrode sheet
[0200] The positive electrode active material, conductive agent (super-P), carbon nanotubes (CNT), and polyvinylidene fluoride (PVDF) prepared above were used to prepare a positive electrode slurry in a mass ratio of 94:1.5:0.5:3. The slurry was coated on a 13μm Al foil and then vacuum dried at 120℃, cold pressed, and cut into strips to obtain the positive electrode sheet.
[0201] (3) Preparation of negative electrode sheet
[0202] A negative electrode slurry was prepared by mixing graphite negative electrode material, conductive agent (Super P), binder (SBR), and thickener (CMC-Na) in a mass ratio of 96.2:0.8:1.8:1.2. The slurry was coated onto an 8μm copper foil and then vacuum dried at 120℃, cold pressed, and cut into strips to obtain the negative electrode sheet.
[0203] (4) Assemble the battery
[0204] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the anode and cathode to provide isolation. After being wound up, they are placed in an outer package, injected with the prepared electrolyte, and then encapsulated, filled with electrolyte, formed, and vented to obtain a lithium-ion battery.
[0205] Those skilled in the art will understand that in the methods described above in the specific embodiments and comparative examples, the order in which the steps are written does not imply a strict execution order and does not constitute any limitation on the implementation process. The specific execution order of each step should be determined by its function and possible internal logic.
[0206] II. Testing Methods
[0207] 1) Gram capacity test
[0208] Using the positive electrode sheet from section "I. Preparation of Secondary Battery" as the positive electrode and a lithium sheet as the negative electrode, a coin cell was assembled. The charge / discharge capacity at a 1C rate current density of 2.8V–4.2V was tested at 25℃.
[0209] Meanwhile, the coulombic efficiency is calculated based on the charge and discharge capacity: first-cycle coulombic efficiency = first-cycle discharge capacity / first-cycle charge capacity × 100%.
[0210] 2) Power performance test
[0211] At 25°C, the lithium-ion battery from the "I. Preparation of Secondary Battery" section was fully charged at a current density of 1C. It was then discharged at current densities of 1C and 20C, respectively. Using the 1C capacity as a reference, the discharge capacity of the lithium-ion battery was tested to obtain its capacity retention rate. The 20C capacity retention rate is calculated as: 20C capacity retention rate / 1C discharge capacity × 100%.
[0212] 3) Cyclic performance test
[0213] The lithium-ion batteries used in the "Preparation of Secondary Batteries" section were subjected to charge-discharge cycle tests at a current density of 5C under a temperature of 25℃, with the voltage range set from 2.8V to 4.2V. The capacity retention rate was calculated as: (First-cycle discharge capacity / Discharge capacity after 1000 cycles) × 100%.
[0214] 4) Chemical composition testing
[0215] Molecular formula confirmation: The molecular formula of the hollow secondary particles was determined by ICP emission spectroscopy.
[0216] The mass content of Li₂CO₃ and LiOH can be determined using the general method for determining acidity and alkalinity with chemical reagents (GB / T 9724-2007). An automated two-step potentiometric titration is performed on the filtrate using dilute hydrochloric acid solution as the titrant. Initially, the following reactions occur: LiOH + HCl = LiCl + H₂O, Li₂CO₃ + HCl = LiHCO₃ + LiCl. With the continuous addition of dilute hydrochloric acid solution, all lithium hydroxide is converted to lithium chloride and water, and all Li₂CO₃ is converted to lithium bicarbonate and lithium chloride. At this point, the pH value is approximately 4.0–5.0, and the potentiometric titrator shows an electrode potential jump point EP1. With further addition of dilute hydrochloric acid, LiHCO₃ + HCl = LiCl + CO₂↑ + H₂O, at which point the pH value is approximately 8.0–9.0, and the potentiometric titrator shows an electrode potential jump point EP2. The content of Li₂CO₃ and LiOH in the sample can be calculated from the amount of dilute hydrochloric acid consumed corresponding to EP1 and EP2.
[0217] III. Experimental Conditions and Test Results
[0218] The main experimental conditions and test results for each experimental group are shown in Tables 1 to 3. Figures 8-10 As shown, for experimental conditions not described, please refer to the above descriptions of the specific embodiments and comparative examples, and they will not be repeated here.
[0219] Table 1.1
[0220]
[0221]
[0222] Table 1.2
[0223]
[0224] Table 2.1
[0225]
[0226]
[0227] Table 2.2
[0228]
[0229] Wherein, the molar percentage of element A refers to its molar percentage in the mixture in step 3).
[0230] Table 3
[0231]
[0232] Figure 7 This is a SEM image of the surface of the positive electrode active material prepared in Example 1 of this application; according to Figure 7 It can be seen that the positive electrode active material prepared in Example 1 exhibits a polycrystalline particle morphology composed of multiple primary small particles.
[0233] Figure 8 This is a SEM image of the cross-section of the positive electrode active material prepared in Example 1 of this application; according to Figure 8 It can be seen that the positive electrode active material prepared in Example 1 has a hollow structure.
[0234] The positive electrode active material exhibits a polycrystalline particle morphology composed of multiple primary small particles, with good sphericity and roundness.
[0235] Figure 9 This is another SEM image of the positive electrode active material prepared in Example 1 of this application; Figure 10 for Figure 9 The energy spectrum at position 20 in the spectrum (taking position 20 in the spectrum as an example, other positions are analyzed using the same method).
[0236] Combination Figure 9 and Figure 10 The weight percentage, weight percentage variance, and atomic percentage of element M corresponding to each site in the cross-section of the positive electrode active material are shown in Table 4.
[0237] Table 4
[0238]
[0239]
[0240] As shown in Table 4, in the positive electrode active material prepared in Example 1 of this application, the content of element M at the grain boundary is greater than the content in the bulk phase of the primary particles.
[0241] Based on Tables 1 to 3 above, a brief analysis is as follows:
[0242] In Examples 1 to 14:
[0243] In Examples 1 to 11, by controlling the appropriate pH value of the solution containing the transition metal salt, the heating time of the solution containing the transition metal salt, and the precipitation reaction time in the preparation process, the k value of the hollow secondary particles can be well controlled within the range of 0.5 to 0.8. In Example 12, the heating time of the solution containing the transition metal salt was relatively long and the precipitation reaction time was relatively short, resulting in a relatively high k value of the hollow secondary particles. In Examples 13 and 14, the pH value of the solution containing the transition metal salt was relatively low, resulting in a relatively low k value of the hollow secondary particles.
[0244] Compared with Examples 1 to 5, the volume average particle size Dv50 of the hollow secondary particles in Example 12 is similar, the k value of the hollow secondary particles in Example 12 is relatively high, and Examples 1 to 5 have higher power performance and cycle performance.
[0245] Compared with Examples 1 to 5, Examples 13 to 14 have similar volume average particle size Dv50 for hollow secondary particles, and the k value of hollow secondary particles in Examples 13 to 14 is relatively low. Examples 1 to 5 have higher power performance and cycle performance.
[0246] Compared with Examples 1 to 5, Examples 6 to 8 have similar k values for hollow secondary particles. The volume average particle size Dv50 of the hollow secondary particles in Examples 1 to 5 is in the range of 2.5 μm to 3.5 μm, while the volume average particle size Dv50 of the hollow secondary particles in Examples 6 to 8 is not in the range of 2.5 μm to 3.5 μm. Examples 1 to 5 have higher power performance and cycle performance.
[0247] Compared with Examples 1 to 5, Examples 9 to 11 are mainly different in the nickel-cobalt-manganese ratio. All examples have good power performance and cycle performance.
[0248] In Examples 1 and 15 through 27:
[0249] Compared with Example 1, Examples 15-16 and Example 25, Example 1 and Examples 15-16 added an appropriate amount of source A, which improved both power performance and cycle performance. Among them, Example 1 and Examples 15-16 had a relatively higher amount of source A added, and Example 1 had better cycle performance and power performance.
[0250] Compared with Examples 17-18, Examples 1 uses a different A source, and each example has better power performance and cycle performance.
[0251] Compared with Comparative Example 1, Examples 1, 19-21 and Examples 21 added an appropriate amount of M source and an appropriate amount of residual alkali, which significantly improved the power performance and cycle performance.
[0252] Compared with Examples 1 and Examples 22 to 24, different M sources were used, and each example had better power performance and cycle performance.
[0253] Compared with Comparative Example 2, the M source in Example 1 is more distributed at the grain boundaries, while the M source in Example 27 is bulk doped. Example 1 can better cooperate with an appropriate amount of residual alkali, resulting in better power performance and cycle performance.
[0254] In Examples 1, 26 to 30:
[0255] Based on the comparison of Examples 1, 26 to 30, it can be seen that the lithium salt ratio and sintering temperature affect the residual alkali content in the positive electrode active material.
[0256] The positive electrode active materials in Examples 1 and 26 to 29 all contain a certain amount of Li2CO3 and LiOH, which can be well combined with element M, and the power performance and cycle performance are significantly improved.
[0257] Compared with Example 1, Example 30 has a lower Li2CO3 content, while Example 1 has significantly better power performance and cycle performance.
[0258] In Examples 1 and 31-41:
[0259] Compared with Example 41, Example 31 to Example 40 has no coating layer, while Example 1 and Example 31 to Example 40 have better power performance and cycle performance.
[0260] Compared with Examples 1, 37-38 and 39-40, the coating layer in Example 39 includes Al but does not include B, the coating layer in Example 40 includes B but does not include Al, the coating layers in Examples 1 and 37-38 include Al and B, Examples 1 and 37-38 have better power performance than Example 39, and Examples 1 and 37-38 have better cycle performance than Example 40.
[0261] Compared with Examples 1 and Examples 31-32, Examples 33-34 have a relatively high content of coating layer, while Example 1 has higher specific capacity and power performance.
[0262] Compared with Examples 36 to 38, Example 1 has a more suitable mass ratio of Al and B, and Example 1 has higher specific capacity and power performance.
[0263] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and not to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application, and they should all be covered within the scope of the claims and specification of this application. In particular, as long as there is no structural conflict, the various technical features mentioned in the embodiments can be combined in any way. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A positive electrode active material, characterized in that, The positive electrode active material comprises hollow secondary particles; The hollow secondary particle includes Li a Ni x Co y Mn z A q M p O b , 0.2≤a≤1.2, 1.8≤b≤2, 0.3≤x≤0.6, 0≤y≤0.4, 0<z≤0.4, 0≤q≤0.02, 0<p≤0.02, element A includes one or more of Ti, Zr, Sr, B, La and Y, and element M includes one or more of W, Mo, Y, La, Zr and Co; The atomic percentage of element M at the grain boundary is greater than or equal to the atomic percentage of element M in the bulk phase of the primary particle, and the distance from the bulk phase to the surface of the primary particle is equal to 5% of the volume average particle size Dv50 of the primary particle; element A is distributed in the hollow secondary particle in a bulk doping manner.
2. The positive electrode active material according to claim 1, characterized in that, The residual alkali in the positive electrode active material includes Li₂CO₃ and LiOH; in the positive electrode active material, the content of Li₂CO₃ is s, the content of LiOH is t, 0.05wt%≤s≤3wt%, 0 <t≤0.4wt%。 3. The positive electrode active material according to claim 2, characterized in that, At least one of the following conditions (a1) and (a2) must be met; (a1) 0.05wt%≤s≤0.4wt%; (a2)0 <t≤0.25wt%。 4. The positive electrode active material according to claim 1 or 2, characterized in that, 0<q≤0.005。 5. The positive electrode active material according to claim 1, characterized in that, 0<p≤0.01。 6. The positive electrode active material according to claim 1, characterized in that, At least one of the following conditions (b1) to (b5) must be met; (b1) The volume average particle size Dv50 of the hollow secondary particles is 2μm~5μm; (b2) The volume average particle size Dv50 of the hollow secondary particles is 2.5 μm to 3.5 μm; (b3) The wall thickness of the hollow secondary particles is 0.2 μm to 1.6 μm; (b4) The ratio of the cavity diameter of the hollow secondary particle to the volume average particle size Dv50 of the hollow secondary particle is k, 0.1≤k≤0.8; (b5) The ratio of the cavity diameter of the hollow secondary particle to the volume average particle size Dv50 of the hollow secondary particle is k, where 0.5≤k≤0.
8.
7. The positive electrode active material according to claim 1, characterized in that, The positive electrode active material further includes a coating layer, which is distributed on at least a portion of the surface of the hollow secondary particles; The coating layer includes Al and / or B elements.
8. The positive electrode active material according to claim 7, characterized in that, In the positive electrode active material, the total content of Al and / or B elements in the coating layer accounts for b of the mass ratio of the positive electrode active material, and satisfies at least one of the following conditions (c1) and (c2); (c1) 0 < b ≤ 5wt%; (c2) 0.1wt%≤b≤2wt%.
9. The positive electrode active material according to claim 7 or 8, characterized in that, In the covering layer, at least one of the following conditions (d1) and (d2) is satisfied; (d1) The mass ratio of Al to B is 1 to 5; (d2) The mass ratio of Al to B is 2 to 2.
5.
10. The positive electrode active material according to claim 1, characterized in that, The true density of the positive electrode active material is ≥4.6 g / cm³. 3 .
11. A positive electrode plate, characterized in that, Includes the positive electrode active material as described in any one of claims 1 to 10.
12. A secondary battery, characterized in that, Including the positive electrode sheet as described in claim 11.
13. An electrical appliance, characterized in that, Includes the secondary battery as described in claim 12.
14. A method for preparing a positive electrode active material as described in any one of claims 1 to 10, characterized in that, include: Heating a solution containing transition metal salts forms a carbonate core; A precipitation reaction occurs on the surface of the carbonate core to obtain a precursor whose core comprises carbonate and whose shell comprises hydroxide. The precursor, lithium salt, material containing element A, and raw material containing element M are mixed and sintered to obtain the hollow secondary particles.
15. The preparation method according to claim 14, characterized in that, It must satisfy at least one of the following conditions (e1) to (e3); (e1) The pH value of the solution containing the transition metal salt is 10.5~12; (e2) The solution containing the transition metal salt is heated for 14 to 25 hours; (e3) The precipitation reaction takes place over a period of 20 to 28 hours.
16. The preparation method according to claim 15, characterized in that, The molar ratio of the precursor to the lithium salt is 1:(1~1.2).
17. The preparation method according to claim 14 or 15, characterized in that, Also includes: The hollow secondary particles are mixed with the raw materials of the coating layer and sintered to obtain a positive electrode active material with a coating layer distributed on at least part of the surface of the hollow secondary particles. The coating layer includes Al and / or B elements.
Citation Information
Patent Citations
Ternary positive electrode material and preparation method thereof
CN112909260A
Porous-structure precursor, hollow-structure oxide and application of porous-structure precursor and hollow-structure oxide in positive electrode material
CN114772556A
Ternary positive electrode material, preparation method and lithium ion battery
CN115385394A